A prospective, observational cohort study of the seasonal dynamics of airway pathogens in the aetiology of exacerbations in COPD. Issue 10 (21st April 2017) - Wilkinson, Tom M A; Aris, Emmanuel; Bourne, Simon; Clarke, Stuart C; Peeters, Mathieu; Pascal, Thierry G; Schoonbroodt, Sonia; Tuck, Andrew C; Kim, Viktoriya; Ostridge, Kristoffer; Staples, Karl J; Williams, Nicholas; et al.
Abstract : Background: The aetiology of acute exacerbations of COPD (AECOPD) is incompletely understood. Understanding the relationship between chronic bacterial airway infection and viral exposure may explain the incidence and seasonality of these events. Methods: In this prospective, observational cohort study (NCT01360398 ), patients with COPD aged 40–85 years underwent sputum sampling monthly and at exacerbation for detection of bacteria and viruses. Results are presented for subjects in the full cohort, followed for 1 year. Interactions between exacerbation occurrence and pathogens were investigated by generalised estimating equation and stratified conditional logistic regression analyses. Findings: The mean exacerbation rate per patient-year was 3.04 (95% CI 2.63 to 3.50). At AECOPD, the most common bacterial species were non-typeable Haemophilus influenzae (NTHi) and Moraxella catarrhalis, and the most common virus was rhinovirus. Logistic regression analyses (culture bacterial detection) showed significant OR for AECOPD occurrence when M. catarrhalis was detected regardless of season (5.09 (95% CI 2.76 to 9.41)). When NTHi was detected, the increased risk of exacerbation was greater in high season (October–March, OR 3.04 (1.80 to 5.13)) than low season (OR 1.22 (0.68 to 2.22)). Bacterial and viral coinfection was more frequent at exacerbation (24.9%) than stable state (8.6%). A significant interaction was detected between NTHi and rhinovirus presence and AECOPD risk (OR 5.18 (1.92 to 13.99); p=0.031). Conclusions: AECOPD aetiology varies with season. Rises in incidence in winter may be driven by increased pathogen presence as well as an interaction between NTHi airway infection and effects of viral infection. Trial registration number: Results, NCT01360398 .